Effects of immigrant background on text comprehension, vocabulary, and reading motivation: A longitudinal study. (February 2015) - Kigel, Rebecca M.; McElvany, Nele; Becker, Michael
Abstract: The purpose of this paper is to examine disparities in important components of reading acquisition in the context of migration. Previous empirical studies showed significant differences in reading skills between students with and without immigrant backgrounds. Data of N = 712 students tested in grades 3, 4, and 6 were analyzed with respect to group differences in reading acquisition. The autoregressive cross-lag panel-model and the latent growth curve models revealed negative effects of immigrant background on the relative position of children in the domains text comprehension and vocabulary as well as a negative effect on relative changes in vocabulary and positive effects on relative changes in reading motivation. Social inequality could not fully explain the identified effects. Immigrant background did not predict absolute growth of text comprehension, vocabulary, and reading motivation. Implications of the findings for research and practice are discussed. Highlights: Immigrant background negatively predicts reading literacy in grade 3. Negative influences on relative changes in rank-order in vocabulary are observable. Positive influences on relative changes in rank-order in motivation are observable. Immigrant background does not predict the absolute growth of reading literacy. Immigrant background does not predict the absolute growth of reading motivation.